Стандартизация робототехнических устройств - Александрова Т. В. Татьяна Викторовна; Громаков Е. И. Евгений Иванович; Зарницын А. Ю. Александр Юрьевич; Лиепиньш А. В. Андрей Вилнисович (2016, 2016)
Заглавие с экрана